Rethinking the benefits and costs of childhood vaccination: the example of the Haemophilus influenzae type b vaccine - Bärnighausen, Till; Bloom, David E.; Canning, David (Vaccine, 2011)
Economic evaluations of health interventions, such as vaccinations, are important tools for informing health policy. Approaching the analysis from the appropriate perspective is critical to ensuring the validity of evaluation results for particular policy decisions. Using the example of cost-benefit analysis (CBA) of Haemophilus influenzae type b (Hib) vaccination, we demonstrate that past economic evaluations have mostly adopted narrow evaluation perspectives, focusing primarily on health gains, health-care cost savings, and reductions in the time costs of caring, while usually ignoring other important benefits including outcome-related productivity gains (improved economic productivity due to prevention of mental and physical disabilities), behavior-related productivity gains (economic growth due to fertility reductions as vaccination improves child survival), and community externalities (herd immunity and prevention of antibiotic resistance). We further show that potential cost reductions that could be attained through changes in the delivery of the Hib vaccine have also generally been ignored in economic evaluations. Future economic evaluations of childhood vaccinations should take full account of benefits and costs, so that policymakers have sufficient information to make well-informed decisions on vaccination implementation.